Cross sections for neutron-deuteron elastic scattering in the energy range 135 - 250 MeV - Ertan, Erol. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
New results for neutron-deuteron elastic scattering cross sections at energies from 135 to 250 MeV and center-of-mass angles from 80 to 130 have been measured at the WNR facility of the Los Alamos Neutron Science Center at the Los Alamos National Laboratory [1, 2]. The measurements were made with a pulsed neutron beam which allowed the use of time-of- ight techniques and with a cryogenic liquid deuterium and liquid hydrogen target. The neutron-proton elastic cross-section data were used for normalization purposes. An array of pure CsI crystal along with a set of thin scintillator detectors used for charged particle identi cation on one side of the beam, and a set of long horizontal plastic scintillator bars were used as a neutron detector wall on the other side of the beam. Our measurements are compared to both previous measurements and theoretical predictions at relevant energies and favors the predictions including three-nucleon forces.
Keywords: Neutrons -- Scattering.